Modeling No-choice Responses in Attribute Based Valuation Surveys - Arianne T. de Blaeij; Paulo A.L.D. Nunes; Jeroen C.J.M. van den Bergh (Fondazione Eni Enrico Mattei (FEEM), 2005)
We examine the impact of providing a no-choice option in an attribute based valuation experiment. The aim of the experiment was to assess monetary values of cockle fishery management practices in the Dutch Wadden Sea for different stakeholder groups, namely Dutch citizens, local residents, and tourists. The current policy debate about the management of the Wadden Sea stresses the fact that individual preferences with respect to cockle-fishery differ. The aim of this paper is to analyze the individual preferences in an objective way. Special attention is given to the influence of including a no-choice option, which is analyzed using a nested logit model. We test whether the full set of policy options can be considered as close substitutes. The estimation results show that the influence of including the no choice option differs among the stakeholders considered.
Keywords: C25; C29; Q22; Q25; Q51; 330; Stakeholder valuation; Stated choice method; Multinomial logit model; Binary logit model; Fischereiressourcen; Küstenregion; Stakeholder; Bewertung; Niederlande